Hubungan Cyberbullying Terhadap Kesehatan Mental Remaja di SMA Dharma Bakti Palembang Tahun 2025: Penelitian - Anugrah Rahmad Hidayat; Riko Sandra Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Adolescents are an age group vulnerable to various psychosocial pressures, including the negative impacts of social media use such as cyberbullying. This digital bullying can cause emotional disturbances that impact mental health, such as anxiety, stress, and depression. This study aims to determine the relationship between cyberbullying and the mental health of adolescents at Dharma Bhakti High School, Palembang in 2025. The study used a quantitative method with a cross-sectional approach. The sample consisted of 149 students selected through simple random sampling. The instruments used were the Cyberbullying Questionnaire (CBQ) item and the Mental Health Inventory (MHI-38). Data analysis was performed using the Chi-Square test. The results showed a relationship between cyberbullying and adolescent mental health (p-value <0.05), where students who experienced cyberbullying tended to have more disturbed mental health. The majority of adolescents experienced cyberbullying at low levels (77.2%), moderate (21.5%), and high (1.3%). The mental health of most adolescents was classified as very good (73.8%), good (22.8%), and poor (3.4%). This study recommends that adolescents use social media more wisely, avoid cyberbullying, and immediately seek support from parents, teachers, or counselors if they become victims.